Analisis Pengaruh Persepsi Mahasiswa Mengenai Karakteristik dan Kepribadian Dosen terhadap Motivasi Kuliah Program Studi Pendidikan Ekonomi Universitas Muhammadiyah Purworejo - Cahyo Apri Setiaji (Jurnal Kualita Pendidikan, 2022)
This study aims to determine the effect of Characteristics (X1) and Lecturer Personality (X2) on Lecture Motivation (Y) of students of the Economic Education Study Program, University of Muhammadiyah Purworejo. This research is a type of quantitative research. The research population was all students of the Economic Education Study Program, University of Muhammadiyah Purworejo totaling 120 people and with an error rate of 5%, the number of samples was 89 people. The sampling technique used is proportionate stratified random sampling, which is the technique used when the population is heterogeneous or consists of stratified groups. The research instrument used a questionnaire with five alternative answers. The test of the instrument used the formula for testing the validity and testing the reliability. The data analysis technique used descriptive and quantitative analysis with simple correlation, multiple correlation, t test, and F test. The results showed that there was a significant influence between Characteristics (X1) and Lecturer Personality (X2) on Lecture Motivation (Y) partially or simultaneously. with values ??respectively 0.001 < 0.05, 0.000 < 0.05, and 0.000 < 0.05. Based on the results of the simple regression test and multiple regression, the hypothesis (Ha) which states that there is a significant influence between Characteristics (X1) and Lecturer Personality (X2) on Lecture Motivation (Y) partially or simultaneously is declared acceptable.